The Tuscarora War : Indians, settlers, and the fight for the Carolina colonies - La Vere, David (North Carolina history & culture anthology., 2013)
At dawn on September 22, 1711, more than 500 Tuscarora, Core, Neuse, Pamlico, Weetock, Machapunga, and Bear River Indian warriors swept down on the unsuspecting European settlers living along the Neuse and Pamlico Rivers of North Carolina. Over the following days, they destroyed hundreds of farms, killed at least 140 men, women, and children, and took about 40 captives. So began the Tuscarora War, North Carolina's bloodiest colonial war and surely one of its most brutal. In this gripping account, the author examines the war through the lens of key players in the conflict, reveals the events that led to it, and traces its far-reaching consequences. The author details the innovative fortifications produced by the Tuscaroras, chronicles the colony's new practice of enslaving all captives and selling them out of country, and shows how both sides drew support from forces far outside the colony's borders. In these ways and others, the author concludes, this merciless war pointed a new direction in the development of the future state of North Carolina. --